2014
DOI: 10.5606/tjr.2014.3550
|View full text |Cite
|
Sign up to set email alerts
|

Is There An Association Between Chronic Urticaria and Fibromyalgia Syndrome?

Abstract: Objectives: Chronic urticaria (CU) and fibromyalgia (FM) are different types of diseases with unclear etiopathogeneses but share many clinical and histochemical features. This study aims to make a recognization on these features and examines whether patients with CU are also affected by FM. Patients and methods:Forty patients with CU and 38 healthy controls were enrolled to this study. All of the participants were assessed according to the 1990 American College of Rheumatology (ACR) classification criteria for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In addition, chronic urticaria patients had more complaints involving chronic widespread pain, anxiety, depression, sleep disturbances, fatigue, morning stiffness, and swollen soft tissues than healthy controls. 23 Thune et al 24 found that 8.3% of patients with psoriasis had FMS. However, they did not compare their results with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, chronic urticaria patients had more complaints involving chronic widespread pain, anxiety, depression, sleep disturbances, fatigue, morning stiffness, and swollen soft tissues than healthy controls. 23 Thune et al 24 found that 8.3% of patients with psoriasis had FMS. However, they did not compare their results with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…A literature search revealed that there are three published studies regarding FMS frequency in chronic urticaria, [21][22][23] and one study in psoriasis. 24 However, to the best of our knowledge, there is no study regarding FMS frequency in acne patients.…”
Section: Discussionmentioning
confidence: 99%